Development And Implementation Of A New Technique For Bert (Bit Error Rate Tester) Using SDR Platform - Hamza, Ekhlas Kadhum (2011)
Hardware/Software (HW/SW) co-design approaches become prospective choice due to its real time operation since these solutions are so flexible that cover extensive complicated systems and reduce time from design to market. Hybrid digital signal processors (DSPs), field programmable gate arrays (FPGAs) and general-purpose processors (GPPs) designs are viable solution for software defined radio (SDR) technology. This thesis demonstrates a practical design and implementation procedure for building a useful, efficient and flexible model of a bit error rate tester (BERT) on physical layer for UHF-band of the digital transceivers by using new architecture in Multi-Core Software-Defined Radio